Human Rights Violation Cases: Challenges and Implications for the Future - Meisi Nuramelia; Robby Marcelinus Sembiring; Indah Syah Putri Harahap; Saidatul Hanna Rambe; Oksari Anastasya Sihaloho (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This research aims to examine several cases of human rights violations that often occur among students. Using qualitative methods with descriptive, this study explores in depth the knowledge, attitudes and experiences of students regarding human rights issues in the context of campus life and society. The collected data was analyzed using the thematic analysis method to identify main patterns in students' understanding of human rights. The research results reveal various student perceptions about cases of human rights violations, challenges in enforcing them, as well as their views on the long-term implications of human rights issues. The main findings indicate a gap between theoretical understanding and practical application of human rights among students, as well as variations in the level of awareness of contemporary human rights issues. This study also identifies the main challenges in education and upholding human rights from a student perspective, including structural, social and cultural barriers. The implications of this research include the importance of strengthening the human rights curriculum in universities, increasing awareness of contemporary human rights issues, and developing strategies to bridge the gap between theoretical understanding and practical implementation of human rights.